How calcium may cause exocytosis in sea urchin eggs. Issue 5 (May 1987) - Whitaker, Michael
Abstract : The process of secretory granule-plasma membrane fusion can be studied in sea urchin eggs. Micromolar calcium concentrations are all that is required to bring about exocytosis in vitro . I discuss recent experiments with sea urchin eggs that concentrate on the biophysical aspects of granule-membrane fusion. The backbone of biological membranes is the lipid bilayer. Sea urchin egg membrane lipids have negatively charged head groups that give rise to an electrical potential at the bilayer-water interface. We have found that this surface potential can affect the calcium required for exocytosis. Effects on the surface potential may also explain why drugs like trifluoperazine and tetracaine inhibit exocytosis: they absorb to the bilayer and reduce the surface potential. The membrane lipids may also be crucial to the formation of the exocytotic pore through which the secretory granule contents are released. We have measured calcium-induced production of the lipid, diacylglycerol. This lipid can induce a phase transition that will promote fusion of apposed lipid bilayers. The process of exocytosis involves the secretory granule core as well as the lipids of the membrane. The osmotic properties of the granule contents lead to swelling of the granule during exocytosis. Swelling promotes the dispersal of the contents as they are extruded through the exocytotic pore. The movements of water and ions during exocytosis may also stabilize the transient fusion intermediate and consolidate the exocytotic pore as fusion occurs.